Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
-0.25
Step-by-step explanation:
→ Find fg(x)
2 ( x + 1 )² = 2x² + 4x + 2
→ Find gf(x)
2x² + 1
→ Equate them
2x² + 1 = 2x² + 4x+ 2
→ Move everything to the right hand side
0 = 4x + 1
→ Solve
x = -0.25
Answer:
[tex]-\frac{1}{4}[/tex]
Step-by-step explanation:
Work out fg(x)
To work out fg(x), put the g function into the f function so, the x in f(x) is equal to the x+1 (from the g function) so:
[tex]2(x+1)^{2} = 2 (x^{2} +2x+1) = 2x^{2} + 4x +2[/tex]
So fg(x) = [tex]2x^{2} + 4x +2[/tex]
Work out gf(x)
Do this by substituting the f(x) equation into the g(x) which is:
[tex](2x^{2} )+1[/tex]
So gf(x) = [tex](2x^{2} )+1[/tex]
Work out x
And since fg(x) = gf(x),
[tex]2x^{2} + 4x +2[/tex] = [tex](2x^{2} )+1[/tex]
4x = -1
x =[tex]-\frac{1}{4}[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.